ANALISIS KEPADATAN BUDIDAYA PADA PERTUMBUHAN, MORFOMETRIK, DAN KANDUNGAN TIMBAL KERANG HIJAU (Perna viridis) DI TAMBAK EKSTENSIF - Ubaidillah, Ubaidillah; Rahim, Andi Rahmad (JARI : Jurnal Akuakultur Rawa Indonesia, 2024)
In Indonesia, particularly in coastal regions, the green mussel Perna viridis is a significant aquaculture product. Green mussels are not only a significant nutritional resource but also act as bioindicators of environmental contamination, particularly the buildup of heavy metals like lead (Pb). Conversely, stocking density is a critical environmental variable that can influence the efficacy of mussel aquaculture. Morphometric growth and heavy metal buildup in mussels can be affected by elevated stocking numbers in aquaculture systems. Consequently, comprehending the effects of varying stocking levels on these two parameters is essential for advancing ecologically sustainable mussel farming strategies. This study seeks to examine the impact of stocking density on the morphometric development and lead (Pb) accumulation in green mussels (Perna viridis) raised in a polyculture system. The study was performed over 21 days in conventional ponds located in Ujungpangkah District, Gresik, utilizing three distinct stocking density treatments: A (10 individuals/m²), B (20 individuals/m²), and C (30 individuals/m²). The mussels' total weight, length, breadth, and Pb concentration were documented on days 0 and 21. The results indicated that mussels in the 10 individuals/m² treatment had considerably enhanced growth relative to those in the 30 individuals/m² treatment. No notable variations were detected in the absolute weight across the treatments. Mussels at the elevated density (30 individuals/m²) collected more Pb on day 1; however, after 21 days, Pb levels decreased. This study's findings indicate that reduced stocking numbers mitigate environmental stress, allowing mussels to more effectively regulate Pb buildup. These variables are crucial for guaranteeing the sustainability of green mussel aquaculture